2016
DOI: 10.1038/ncomms12453
|View full text |Cite
|
Sign up to set email alerts
|

Local adaptation of a bacterium is as important as its presence in structuring a natural microbial community

Abstract: Local adaptation of a species can affect community composition, yet the importance of local adaptation compared with species presence per se is unknown. Here we determine how a compost bacterial community exposed to elevated temperature changes over 2 months as a result of the presence of a focal bacterium, Pseudomonas fluorescens SBW25, that had been pre-adapted or not to the compost for 48 days. The effect of local adaptation on community composition is as great as the effect of species presence per se, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 54 publications
5
62
0
Order By: Relevance
“…A similar finding was reported in previous studies in which compositional shifts only occurred when communities were invaded at early stages or when supplied with additional resources (Symons & Arnott 2014;Mallon et al 2015). The result is consistent with a role for priority effects, in both bacterial (Tan et al 2012;G omez et al 2016) and studies of larger organisms (Fukami 2015;Pantel et al 2015); where early invaders are able to utilise existing resources to either monopolise nutrients or to create new niches (e.g. by releasing secondary metabolites), but that such options become closed to them at later stages of succession.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…A similar finding was reported in previous studies in which compositional shifts only occurred when communities were invaded at early stages or when supplied with additional resources (Symons & Arnott 2014;Mallon et al 2015). The result is consistent with a role for priority effects, in both bacterial (Tan et al 2012;G omez et al 2016) and studies of larger organisms (Fukami 2015;Pantel et al 2015); where early invaders are able to utilise existing resources to either monopolise nutrients or to create new niches (e.g. by releasing secondary metabolites), but that such options become closed to them at later stages of succession.…”
Section: Discussionsupporting
confidence: 91%
“…; Gómez et al . ) and studies of larger organisms (Fukami ; Pantel et al . ); where early invaders are able to utilise existing resources to either monopolise nutrients or to create new niches (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies use phenotypically differentiated individuals shown or assumed to be genetically determined and isolated from contrasting habitats (e.g., Walsh et al, ) or generated through experimental evolution (e.g., Pantel et al, ) and quantify effects on population dynamics, species composition or ecosystem features. Others, mainly studies on microbial and unicellular organisms, quantify eco‐evolutionary feedbacks as evolution proceeds (Becks, Ellner, Jones, & Hairston, ; Fukami et al, ; Gómez et al, ; Yoshida et al, ). Many of these proof‐of‐principle experiments demonstrate striking effects of evolutionary trait change on population dynamics and composition (Brunner et al, ; Fukami et al, ), species interactions (Becks et al, ; Friman, Guzman, Reuman, & Bell, ; Yoshida et al, ), community composition (Gómez et al, ; Pantel et al, ; terHorst et al, ) and ecosystem features (Bassar et al, ; Harmon et al, ).…”
Section: An Ecologist's Perspective On Eco‐evolutionary Dynamicsmentioning
confidence: 99%
“…Intraspecific effects can be strong even contrasted with traditional ecological factors like presence of a dominant species (Bailey et al, 2009b;Palkovacs et al, 2015;Gómez et al, 2016) and habitat size (Farkas et al, 2013). A typical study design is a ''common gardening'' experiment (sensu Matthews et al, 2011), in which one tests the ecological impacts of intraspecific trait variants in a common environmental context (e.g., Schweitzer et al, 2004;Palkovacs and Post, 2009;Ingram et al, 2011;Lundsgaard-Hansen et al, 2014;Fryxell et al, 2015;Rudman and Schluter, 2016).…”
mentioning
confidence: 99%